Ukraine : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper examines the main factors explaining Ukraine's growth performance so far, assesses whether the recent recovery is sustainable, and provides a quantitative analysis of long-term growth prospects. It finds that the recent recovery is not yet self-sustaining and estimates that long-term per capita GDP growth of 4-5 percent per year would be possible only if structural reforms are accelerated. The paper also discusses how the shadow economy has been measured in Ukraine and compares the results with studies of other transition economies.